PENGEMBANGAN SISTEM KEUANGAN LEMBAGA NON-FORMAL DENGAN MENGGUNAKAN APLIKASI MICROSOFT ACCES - Mita Indriani; Purwanto (khidmatan, 2024)
Madrasah Diniyah (MD) Nibrosul Athfal, established in 2006 in Krutuk Hamlet as a non-formal religious education institution, faces significant challenges in its financial governance. This research and community service initiative revealed that financial recording was still being conducted manually, often leading to difficulties and inaccuracies. Furthermore, the management of daily financial notes was frequently handled by the students (santri) themselves, resulting in sub-optimal financial management. Addressing these shortcomings, the program aimed to transform the manual financial system into a digital one to assist in effective financial administration. The methodology employed was the Asset-Based Community Development (ABCD) approach, with data collected through interviews and Focus Group Discussions (FGD) to thoroughly analyze institutional needs. The core solution implemented was the development of a recording system based on the Microsoft Access Application. The results demonstrate that the transition from a manual to a digital system successfully organized and regulated the financial system at MD Nibrosul Athfal, significantly increasing recording efficiency and generating more accountable financial reports.